Silver meal heuristic method planning and controlling of cracker production inventory in the assisted business units of the BNN community foundation - Sari, Della Arsita; Rima, Rima Aprilia (Universitas Islam Negeri Raden Intan Lampung, 2024)
Inventory control is a production activity that involves planning the amount, time, or cost that must be controlled to obtain a minimum cost and no loss. At the BNN Community Foundation Building Unit, when producing crackers, the production process was disrupted because the available raw materials did not meet production requirements. This study aims to find out the planning and control of raw materials in producing crackers and compare the company's calculation results with the Silver Meal Heuristic method. In this calculation using the data of 5 raw materials and the main requirements in the production process for three months, the result obtained in the calculation with the heuristic silver meal method obtained a minimum result of IDR 27,488,580. When compared to the calculation from the company for three months of production cost expenses, the calculation using the method silverware heuristic can save costs up to IDR 52,19,420. This proves that the calculation using the silver meal heuristic method is better used because it can control the total cost that the factory has to bear in producing crackers.